Analisis Dimensi Kualitas Pelayanan Publik di Era Otonomi Daerah: Studi Kasus Kantor Camat Sinaboi - Dinda Asro Alfayadh; Virna Museliza; Sitti Rahmah (Policy, Law and Political Research Center, 2025)
Subdistrict is a government agency directly under the regency, so it can be said that the success of development also depends on the extent of participation of the local community and the subdistrict government apparatus in planning the development. In addition to being the implementer and planner of community service programs in administrative and population matters, which are the authority of the subdistrict. The Sinaboi Subdistrict Office in Rokan Hilir Regency is a regional apparatus that carries out regional autonomy and assistance matters in the subdistrict to meet the lack of adequate facilities and infrastructure in the subdistrict area. The objective is to analyze the quality and effectiveness of services at the Sinabo Subdistrict Office Sinaboi Subdistrict Office, Rokan Hilir Regency. This research uses a qualitative descriptive method, with data obtained from observations, interviews, and documentation. The results of the research show that, overall, the quality and effectiveness of services at the Sinaboi Subdistrict Office are very good. This is indicated by the results of interviews with community members in Sinaboi Subdistrict, Rokan Hilir District. The service quality is very good, easy, and fast. The community greatly appreciates the services provided by the Sinaboi Subdistrict Office, which greatly supports the ease of service at the Sinaboi Subdistrict Office in Rokan Hilir District.